Biostratigraphy and paleoenvironment studies of shales from Owan-1 Well, Niger Delta Basin, Nigeria - Abdulrasaq Haruna; Jamiudeen Raji; Yusuf Jimoh; James Adeoye; Olatunji Alu; Abdullahi Badmus; Babatunde Garba (Journal of Nigerian Society of Physical Sciences)
An integrated standard sedimentological, foraminifera, and palynological investigations were carried out on twenty (20) ditch-cutting samples from Owan-1 Well in the Niger Delta Basin, with the depth range from 23 – 456 meters to determine the relative age and depositional environment of the strata penetrated by the well. Standard foraminifera preparation techniques involving sample disaggregation and washing through a 63-micron mesh sieve, drying, and picking of the foraminifera and accessory fauna were employed. Palynological slides were prepared following standard palynological preparation procedures of sample maceration with hydrochloric (HCl) and hydrofluoric (HF) acids. The sedimentological analysis led to the establishment of six (6) lithofacies units comprising shale, claystone, clayey siltstone, fine-grained sandstone, conglomeratic sandstone, and siltstone. Poorly diverse assemblages of benthonic foraminifera with a total of eight (8) species were recorded in which seven (7) species (88%) are calcareous and one (1) arenaceous (12%) while planktic foraminifera are generally absent. Foraminifera species such as Anomalinoides alazanensis, Lenticulina grandis, Ammodiscus glabratus, Valvulineria rugosa, Valvulineria jacksonensis, species of Anomalina, Cibicides and Verneuilina were recovered. Fairly abundant and diverse palynomorphs were recovered from the samples. The palynomorphs were quantitatively dominated by land-derived species such as Verrucatosporites usmensis, Monocolpites sp., and Monoporites annulatus as the diagnostic species.  The abundance of massive, dark, and calcareous shales suggests that the studied interval belongs to the marine Akata Formation of the Niger Delta Basin. Foraminifera and palynological results reveal that the studied interval was deposited during the Middle Eocene Epoch corresponding to P470 and P450 Pollen Zonation. Hence, the sediments penetrated by the well were suggested to be deposited in littoral, inner, and middle neritic corresponding to marginal, shallow, and deep marine environments.